Tata Kelola Destinasi Pariwisata Desa Tenganan Pegringsingan, Karangasem-Bali - I Nyoman Arto Suprapto; Moh Agus Sutiarso; Ni Luh Dian Febrianti Wiratmi (Ganaya : Jurnal Ilmu Sosial dan Humaniora, 2021)
Tenganan Pegringsingan village is a traditional village that has been declared as one of the tourist villages in Karangasem Regency. Tenganan Pegringsingan tourism village has a cultural-based tourism village concept. The purpose of this research is to examine the governance of tourism and to find out the perceptions of tourists about the tourism product at the village. This study uses a qualitative descriptive method to explain tourism governance and the perceptions of tourists who have visited. The results showed that the tourism governance in the village of Tenganan Pegringsingan is currently classified as less than optimal. This can be seen from the absence of careful planning for the development of village tourism and the absence of a clear tourism village management organization. The perception of tourists on the existence of tourist attractions, accessibility, amenities and ancillery services owned by Tenganan Pegringsingan village showed good value.